2008
DOI: 10.1007/s00253-008-1701-1
|View full text |Cite
|
Sign up to set email alerts
|

The absence of effect of gene copy number and mRNA level on the amount of mAb secretion from mammalian cells

Abstract: Recombinant human antibody production represents a major growing class of biopharmaceuticals based on the technological progress within the last decades especially in CHO cells. The HIV neutralizing human monoclonal antibody 2F5 was developed as hybridoma from human lymphocyte preparations. In order to estimate the potential of recombinant 2F5-expressing CHO cells, we generated different recombinant CHO cell lines by varying regulatory sequences, the codon usage, the signal peptides, and the transfection techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…However they had lower transcription and expression level. The results are consistent with former studies in which GCN did not reflect the content of mRNA [36]. Studies have shown that mammalian cells lines which contain higher copies of the heterologous plasmids were are susceptible to silencing [37, 38], and early methylation coincide with high transgene copy numbers [26].…”
Section: Discussionsupporting
confidence: 91%
“…However they had lower transcription and expression level. The results are consistent with former studies in which GCN did not reflect the content of mRNA [36]. Studies have shown that mammalian cells lines which contain higher copies of the heterologous plasmids were are susceptible to silencing [37, 38], and early methylation coincide with high transgene copy numbers [26].…”
Section: Discussionsupporting
confidence: 91%
“…In both, CHO as well as HEK cells, IgM-012 producing cell line showed several times lower specific productivity and antibody titer levels than IgM-617 producing cell line (sevenfold difference in CHO cells, 22-fold difference in HEK cells). Although CHO and HEK IgM-617 cell lines manifested same or higher gene copy numbers for HC, LC, and JC coding genes than IgM-012 cell lines (with dramatically higher values for CHO IgM-617 cells), this fact is not reflected at the transgene transcript and specific productivity level, similarly as shown previously (Lattenmayer et al 2007b;Reisinger et al 2008). These studies as well as our results indicated that many of coding gene copies are probably incorporated into places, which are not as favorable for transcription initiation or are not active at all.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, there are potential bottlenecks for the optimum expression of every heterologous protein including promoter strength (Kim et al 2009), the gene copy number (Vassileva et al 2001), the codon usage of recombinant gene (Xu et al 2010), and finally processing in ER and Golgi and secretion out of cell in case of secretary protein (Inan et al 2006). Based on previous experiments, each of these factors can be considered for elevating the heterologous protein expression, though there are no reliable means of predicting the precise effect of each factor (Strausberg and Strausberg, 2001;Luo et al 2006;Geymonat et al 2007;Ramachandran et al 2008;Reisinger et al 2008;PĂ©rez-GarcĂ­a et al 2010). AAT protein was expressed and partially characterized in the previous work (Arjmand et al 2011).…”
Section: Fig 5 Graphs Related To Comparison Of Secreted and Intracelmentioning
confidence: 99%